2019
DOI: 10.1080/21645515.2019.1565269
|View full text |Cite
|
Sign up to set email alerts
|

The use of cell-mediated immunity for the evaluation of influenza vaccines: an upcoming necessity

Abstract: Influenza vaccines are a fundamental tool for preventing the disease and reducing its consequences, particularly in specific high-risk groups. In order to be licensed, influenza vaccines have to meet strict criteria established by European Medicines Agency. Although the licensure of influenza vaccines started 65 years ago, Hemagglutination Inhibition and Single Radial Hemolysis are the only serological assays that can ascertain correlates of protection. However, they present evident limitations. The present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 119 publications
0
23
0
Order By: Relevance
“…Many lectins with antiviral properties have been discovered, with most being high-mannose-binding lectins directed against the heavily glycosylated human immunodeficiency virus (HIV) ( Mitchell et al., 2017 ). Griffithsin (GRFT), a lectin isolated from the red algae Griffithsia sp., is currently in clinical trials as a topical vaginal gel for the prevention of HIV ( Gianchecchi et al., 2019 ). A major obstacle for exogenous lectin treatment in vivo is their potential toxicity, as they may also recognize sugar moieties on host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many lectins with antiviral properties have been discovered, with most being high-mannose-binding lectins directed against the heavily glycosylated human immunodeficiency virus (HIV) ( Mitchell et al., 2017 ). Griffithsin (GRFT), a lectin isolated from the red algae Griffithsia sp., is currently in clinical trials as a topical vaginal gel for the prevention of HIV ( Gianchecchi et al., 2019 ). A major obstacle for exogenous lectin treatment in vivo is their potential toxicity, as they may also recognize sugar moieties on host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ansaldi et al [32], for example, showed that in elderly subjects immunized with an adjuvanted trivalent IV, the correlation coefficient r between the mean-fold increase in neutralizing antibody titers (from pre-to post-vaccination) and the antigenic distance of several drifted A(H3N2) strains was substantially higher than the r between the corresponding mean-fold increase in HAI titers (0.701 vs. 0.501). Analogously, the use of CMI, which plays a crucial role in protecting against influenza by establishing the long-term immunological memory [18], may also positively "differentiate" the adjuvanted formulations from their non-adjuvanted counterparts. For instance, Zedda et al [33] found that adding an adjuvant to standard IVs induced a larger expansion of vaccine-specific CD4+ cells, and that this advantage was evident with regard to the drifted heterologous strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, cell-mediated immunity (CMI) plays an important role in the host immune response in protecting against virus-related illness and in establishing long-term immunological memory. Although correlates of protection are not currently available for CMI, it would be advisable to investigate this kind of immunological response with a view to evaluating next-generation vaccines [18].…”
Section: Introductionmentioning
confidence: 99%
“…SRH detects the concentration of influenza-targeting antibodies by measuring a ring of hemolysis caused by the antibody-virus-erythrocyte complex activating the complement system [90]. While this method measures all serum antibodies against influenza surface antigens, it still does not recognize local mucosal immunity or cellmediated immunity, such as immunization strategies that target M1 or NP [91].…”
Section: Challenges For Universal Influenza Vaccine Developmentmentioning
confidence: 99%